Comparison of Bar Formation Mechanisms. II. Does a Tidally Induced Bar Grow Faster than an Internally Developed Bar? - Yirui Zheng; Juntai Shen; Xufen Wu; Bin-Hui Chen (The Astrophysical Journal)
Bar structures can form internally due to the instability of their host galaxies or externally due to perturbations from other galaxies. We systematically quantify the growth timescales ( τ _bar ) of bars formed through these two mechanisms with a series of controlled N -body simulations. In galaxies susceptible to bar instability, tidally induced bars display τ _bar values comparable to those of internally developed bars within the same disk. Tidal perturbations promote (delay) bar formation by advancing (postponing) its onset, but the growth rate of the bar structure remains largely unchanged. In these interaction scenarios, the bar formation is still driven primarily by the galaxy’s internal nature, which remains unaffected by tidal perturbations. As the external perturbation wave reaches the galaxy’s center, it evokes a “seed bar” that is then swing amplified. In this scenario, the onset of bar formation is advanced. Conversely, bar formation may be delayed if the external perturbation wave is out of phase with the preexisting spontaneously developed “seed bar,” which causes destructive interference and limits bar growth. In the hot disk model that resists bar formation in isolation, the τ _bar of the tidally forced bar correlates with the strength of the perturbation. The bar growth in this model deviates from an exponential profile and is better described by a linear function. The varied τ _bar and the preference for linear growth contrast with bars formed in galaxies inherently susceptible to bar instability. These tidally forced bars may not adhere to the swing amplification mechanism that predicts exponential bar growth.